Marrying fiscal rules & investment: A central fiscal capacity for Europe - Christopher Schang; Francesca Vinci (European Central Bank (ECB), 2024)
The European fiscal governance framework remains incomplete, hindering policy coordination during economic shocks and affecting the transmission of the single monetary policy. High public debt and low public investment worsen resilience across Member States. Many policymakers, institutions, and academics support establishing a central fiscal capacity (CFC) as a solution. Against this backdrop, we propose a framework to assess a CFC in the euro area, aimed at stabilizing the business cycle, promoting sovereign debt sustainability, and reducing procyclicality in public investment. Our two-region DSGE model with a permanent CFC allocates resources based on the relative output gap while earmarking funds for public investment and imposing fiscal adjustment requirements for the high-debt region. The CFC enhances business cycle stabilization for both regions and significantly reduces the welfare cost of fluctuations. We also explore European bond issuance and a supranational investment strategy to address investment needs through European Public Goods.
Keywords: E12; E32; E62; F45; 330; EU Governance; Public Debt Sustainability; Macroeconomic Stabilisation; European Public Goods